Analisis Variabel Penentu Keberlanjutan TPA Jalupang Kabupaten Karawang: Perspektif Masyarakat melalui Structural Equation Modeling (SEM): Indonesia - Dewi, Ninne Sevtiana; Widyarsana, I Made Wahyu (UII, 2025)
Jalupang Landfill is the only official final disposal facility in Karawang Regency, which is still operated using an open dumping system. This management practice has created several environmental issues, including a fire incident in October 2023, and has raised concerns about the sustainability of its operations. This study was conducted to identify the variables that influence the sustainability of Jalupang Landfill by employing a reflective Structural Equation Modeling (SEM) approach. Primary data were collected through questionnaires distributed to 100 respondents across nine districts who are involved in waste transportation to the landfill. The questionnaire applied a Likert scale and was analyzed using SmartPLS 4.0 through a series of tests, including model fit, construct validity, and path coefficient analysis. The results indicated that the developed model met the fit criteria, with an R² value of 0.622 or 62.2%. The regulatory variable was found to be the most dominant factor, with a path coefficient of 0.400 (p-value = 0.002), followed by the financing variable with a coefficient of 0.286 (p-value = 0.041). These findings highlight that the sustainability of Jalupang Landfill is largely determined by strengthening regulatory aspects and ensuring adequate financial support.